2017
DOI: 10.1016/j.jseaes.2016.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Provenance of a large Lower Cretaceous turbidite submarine fan complex on the active Laurasian margin: Central Pontides, northern Turkey

Abstract: The Pontides formed the southern active margin of Laurasia during the Mesozoic. They became separated from mainland Laurasia during the Late Cretaceous, with the opening of the Black Sea as an oceanic back-arc basin. During the Early Cretaceous, a large submarine turbidite fan complex developed in the Central Pontides. The turbidites cover an area of 400 km by 90 km with a thickness of more than 2 km. We have investigated the provenance of these turbidites-the Çağlayan Formation-using paleocurrent measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 86 publications
4
44
0
Order By: Relevance
“…In this study, we report new U–Pb detrital zircon ages, petrographic data, and paleocurrent measurements from the Upper Cretaceous (Campanian‐Maastrichtian) turbidites. To highlight the differences existing between turbidites deposited in the central Pontides before and after the oceanic opening of the Black Sea and also to better constrain the timing of the opening of the Black Sea, we compare our new results with those obtained by Akdoğan et al () and Okay et al () from the Lower Cretaceous turbidites.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In this study, we report new U–Pb detrital zircon ages, petrographic data, and paleocurrent measurements from the Upper Cretaceous (Campanian‐Maastrichtian) turbidites. To highlight the differences existing between turbidites deposited in the central Pontides before and after the oceanic opening of the Black Sea and also to better constrain the timing of the opening of the Black Sea, we compare our new results with those obtained by Akdoğan et al () and Okay et al () from the Lower Cretaceous turbidites.…”
Section: Introductionmentioning
confidence: 91%
“…During the Mesozoic, the Pontides constituted the southern active margin of the Laurasia and experienced complex successive subduction‐accretion events (Okay & Nikishin, ). The Lower Cretaceous basinal sequence in the central Pontides is represented by a submarine turbidite fan complex developed on the northern active margin of the Tethys Ocean (Akdoğan et al, ; Aygül et al, , ; Okay et al, , ). Recently, Akdoğan et al () and Okay et al () identified detrital zircons of Archean and Paleoproterozoic ages from these turbidites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Albian volcaniclastic sandstones are reported from the central Sakarya Basin (Yilmaz, ); however, Albian magmatic rocks are not known from the Pontides (Akdoğan et al, ). The virtual absence of Cenomanian to Coniacian zircons in the intrabasinal sediments indicates lack of contemporaneous magmatism, which is in keeping with the stratigraphic sequence in the central Sakarya Basin, where magmatism starts in the Campanian.…”
Section: Alacaatlı Olistostromes: Mass Flows With Pelagic Limestone Bmentioning
confidence: 99%
“…During the Middle Jurassic a magmatic arc developed above the Sakarya Zone as evident from granitoids with associated LP/HT metamorphic rocks and arc volcanic rocks (Çimen et al, 2016;Okay et al, 2014;Yılmaz & Boztuğ, 1986). This composite basement was unconformably overlain by Upper Jurassic limestones and Lower Cretaceous turbidites (Akdoğan et al, 2017;Hippolyte et al, 2010;Okay et al, 2013;Tüysüz, 1999).…”
Section: Geologic Settingmentioning
confidence: 99%